Thermodynamic modelling and parametric study of a low temperature vapour compression-absorption system based on modified Gouy-Stodola equation. (1st January 2015) - Jain, Vaibhav; Sachdeva, Gulshan; Kachhwaha, S.S.
Abstract: Present paper thermodynamically analyses a VCAS (vapour compression-absorption system) with carbon dioxide (compression section) and ammonia-water (absorption section) as refrigerants and determines the optimal condensing temperature of cascade condenser using modified Gouy-Stodola equation. The optimum cascade condenser temperature is found to be −13 °C for 175 kW refrigeration capacity at an evaporator temperature of −45 °C and condenser temperature of 35 °C. The optimum cascade condenser temperature maximises the overall COP, rational efficiency and minimises the total irreversibility rate of the VCAS system. The value of optimum condensing temperature and its corresponding maximum COP, and minimum irreversibility rate are discussed for a wide range of operating conditions. Further, a comparative study of TSVCS (two stage vapour compression system) used for low temperature refrigeration applications with VCAS shows that at design point, primary energy consumption is reduced by 60.6% and electrical COP is improved by 153.6% in VCAS as compared to conventional TSVCS. But the total irreversibility rate of VCAS is 38.4% higher than the TSVCS due to the use of low grade energy in vapour absorption system and hence the rational efficiency of VCAS is 14% low. Highlights: Optimum cascade condenser temperature with modified Gouy-Stodola law is analysed. It maximises COP, rational efficiency and minimises total irreversibility. 60.6% of primary energy is saved by cascaded absorption system. Electrical COP is improved by 153.6% with cascaded absorption system.